1999
DOI: 10.1580/1080-6032(1999)010[0152:mmritm]2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Medical mountain rescue in the Mont-Blanc massif

Abstract: Because of its peculiar geographic location beneath Mont-Blanc, the Chamonix Hospital plays an important role in the management of mountaineering- and skiing-related traumatic injuries. The authors, thanks to the study of 5200 mountain rescue medical reports, set out to explain the different aspects of this activity: epidemiology, specific equipment, care in the field, reception and primary survey, dispatching, common therapeutic attitudes, progress, and results. In the dangerous environment of the high mounta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
3

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 6 publications
2
30
0
3
Order By: Relevance
“…Such a helicopter must be staffed by appropriate mountain rescue and medically-trained personnel (see ICAR recommendation no. 3, Qualifications for Emergency Doctors in Mountain Rescue Operations: "must be comfortable in exposed situations ... conscious of his own safety ... able to work under extreme conditions", Rammlmair et al, 2002) who are part of the official emergency medical system, preferably emergency doctors, with appropriate rescue and medical equipment (Durrer, 1993;Marsigny et al, 1999;Demartines et al, 1991;Dalton et al, 1992).…”
Section: Activation and Rational Use Of Helicopters In Mountain Rescuementioning
confidence: 99%
“…Such a helicopter must be staffed by appropriate mountain rescue and medically-trained personnel (see ICAR recommendation no. 3, Qualifications for Emergency Doctors in Mountain Rescue Operations: "must be comfortable in exposed situations ... conscious of his own safety ... able to work under extreme conditions", Rammlmair et al, 2002) who are part of the official emergency medical system, preferably emergency doctors, with appropriate rescue and medical equipment (Durrer, 1993;Marsigny et al, 1999;Demartines et al, 1991;Dalton et al, 1992).…”
Section: Activation and Rational Use Of Helicopters In Mountain Rescuementioning
confidence: 99%
“…We surmise that the advantages of a helicopter emergency medical service (HEMS) that have already been described will be even more pertinent in mountain rescue, as the path to and from the incident site may be dangerous or take many hours (Butler et al, 2010;Thomas, 2007). A helicopter therefore plays a significant part in an effective modern mountain rescue service (Marsigny et al, 1999;Tomazin, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…25 A similar study conducted on Mount Blanc found that the death rate of mountaineers scaling the mountain was 12%. 26 These fatalities were often due to equipment failure, panic, poor judgment, overconfidence and avalanches. However, the greatest cause of casualties was as a result of falls; high altitude illness in trekkers could conceivably have contributed to some of these fatal falls.…”
Section: Mountaineering and Trekkingmentioning
confidence: 99%